Spring Water of an Alpine Karst Aquifer Is Dominated by a Taxonomically Stable but Discharge-Responsive Bacterial Community - Savio, Domenico; Stadler, Philipp; Reischer, Georg H.; Demeter, Katalin; Linke, Rita B.; Blaschke, Alfred P.; Mach, Robert L.; Kirschner, Alexander K. T.; Stadler, Hermann; Farnleitner, Andreas H. (Frontiers in Microbiology, 2019)
Alpine karst aquifers are important groundwater resources for the provision of drinking water around the world. Yet, due to difficult accessibility and long-standing methodological limitations, the microbiology of these systems has long been understudied. The aim of the present study was to investigate the structure and dynamics of bacterial communities in spring water of an alpine limestone karst aquifer (LKAS2) under different hydrological conditions (base vs. event flow). The study was based on 16S rRNA gene amplicon sequencing, study design and sample selection were guided by hydrology and pollution microbiology data. Spanning more than 27 months, our analyses revealed a taxonomically highly stable bacterial community, comprising high proportions of yet uncultivated bacteria in the suspended bacterial community fraction. Only the three candidate phyla Parcubacteria (OD1), Gracilibacteria (GN02), Doudnabacteria (SM2F11) together with Proteobacteria and Bacteroidetes contributed between 70.0 and 88.4 % of total reads throughout the investigation period. A core-community of 300 OTUs consistently contributed between 37.6 and 56.3 % of total reads, further supporting the hypothesis of a high temporal stability in the bacterial community in the spring water. Nonetheless, a detectable response in the bacterial community structure of the spring water was discernible during a high-discharge event. Sequence reads affiliated to the class Flavobacteriia clearly increased from a mean proportion of 2.3 % during baseflow to a maximum of 12.7 % during the early phase of the studied high-discharge event, suggesting direct impacts from changing hydrological conditions on the bacterial community structure in the spring water. This was further supported by an incline of species richness (Chao 1) at higher discharge. The combination of these observations also allowed the identification and characterization of three different discharge classes (Q1-Q3). In conclusion, we found a taxonomically stable bacterial community prevailing over more than two years in spring waters from an alpine karst aquifer. Clear response to changing discharge conditions could be detected for particular bacterial groups, whereas the most responsive group – bacteria affiliated to the class of Flavobacteriia – might harbor potential as a valuable natural indicator of ‘system disturbances’ in karst aquifers.